Frekuensi dan Kesadaran Siswa SMA Pembangunan Laboratorium UNP dalam Pelaksanaan Shalat - Cisia Padila; Wirdati Wirdati (Prodi Pendidikan Keagamaan Islam, 2022)
Prayer is one of the obligations of a believer to his Lord. Prayer has various virtues and wisdom in terms of religion, psychology, and social society. So, prayer is the most important worship in Islam. Basically a Muslim must make prayer a necessity and obligation, but in reality there are still many Muslims who do not pray, especially fardhu prayers. This study aims to see the frequency and awareness of students about their prayers. This study used descriptive quantitative methods, with data collection methods through questionnaires distributed to 71 students from a total population of 247 students then the data obtained were processed using the SPSS version 21 application to clearly see the frequency and awareness of the student's prayer obligations. The results of this study indicate that the prayers performed by students are classified as good, but their implementation is still negligent in terms of time. It is hoped that there will be further research to overcome students' negligence and ignorance of the meaning of prayer readings.